Pengaruh Budaya Terhadap Pilihan Penerjemahan: Analisis Teks Iklan dari Bahasa Inggris ke Bahasa Indonesia - Yani, Muhamad; Hadi, Muhammad Zaki Pahrul; Nurjanah, Ratih Laily (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the impact of cultural factors on translation choices in English-language advertising texts. In today’s global marketplace, advertisements function not only as persuasive linguistic tools but also as cultural products that reflect and shape social values. Therefore, translating advertisements requires more than linguistic accuracy—it demands a deep understanding of both source and target cultures. Using a qualitative approach and drawing on theories such as dynamic equivalence and cultural translation, this research analyzes English advertisements and their translations across diverse cultural contexts. The analysis focuses on cultural dimensions such as communication context (high vs. low), individualism vs. collectivism, and power distance. The Findings indicate that cultural aspects such as phrases, humor, and a local symbol often can not be translated directly. Therefore, strategies like adaptation, localization, and cultural substitutions are used to keep the relevance and appeal of the message.  This research affirms that the translator's function as a cultural mediator who must consider both the meaning and the sensitivity of the target audience. This Study also emphasizes the importance of cultural competence and collaboration with cultural consultants or native speakers to guarantee the accuracy and cross-cultural respect. In conclusion, a balanced translation approach between faithfulness to the source message and cultural acceptance is highly important in the context of global communication.